Social Welfare & Inequality: The U.S. - Michael Reisch (Social Work and Society, 2019)
Over the past four decades, socio-economic inequality in the U.S. has reached unprecedented proportions. Its consequences extend far beyond the economic realm; they produce widespread disparities in education, employment, health care, and housing. In some cities, the difference in life expectancy varies as much as 30 years between residents of rich and poor neighborhoods.  Persistent inequality also threatens to undermine the foundations of political democracy. Explanations for these phenomena include (1) the changing character of the global economy; (2) the decline of unions and wage stagnation; (3) dramatic shifts in U.S. tax policy; (4) the erosion of the limited U.S. welfare state; and (5) institutional racism and sexism. To date, policy solutions have largely failed to reduce the inequality gap for several reasons. They have been limited, piecemeal efforts without a unifying strategy and have not addressed either the structural causes or the multifaceted nature of the problem. Political opponents have attacked even modest reform proposals. This paper will summarize the major causes of inequality in the U.S., with particular attention to changes in welfare policy, and briefly discuss the implications for the future of social welfare.